A Vital Challenge to Materialism. (10th February 2016) - Mulder, Jesse M.
Abstract: Life poses a threat to materialism. To understand the phenomena of animate nature, we make use of a teleological form of explanation that is peculiar to biology, of explanations in terms of what I call the 'vital categories' – and this holds even for accounts of underlying physico-chemical 'mechanisms'. The materialist claims that this teleological form of explanation does not capture what is metaphysically fundamental, whereas her preferred physical form of explanation does. In this essay, I do three things. (1) I argue that the 'vital categories', such as life form and life-process, do not reduce to the 'physical categories' and show that there are no grounds for the materialist's metaphysically limiting claim; (2) I sketch a positive view on how vital and physical explanations can both apply to a given phenomenon, and on how they interrelate; and (3) I show that this view meshes nicely with evolutionary theory, despite being committed to a form of 'biological essentialism'.